2011
DOI: 10.1080/17441692.2010.539572
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating social and health inequities: Community participation and Chagas disease in rural Argentina

Abstract: Chagas disease (CD) causes 12,500 deaths annually in Latin America. As a neglected disease primarily associated with poverty, it is a major driver of health inequity. Argentina's efforts to control vector transmission have been unsuccessful. Using new survey data (n=400 households), we compare the social patterning of the burden of CD by examining socio-demographic predictors of self-reported CD and the presence of vinchucas in two areas of rural northern Argentina known to have experienced different intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…Four papers on Chagas’ disease met the inclusion criteria (Brazil [GDB #1] two [ 82 , 83 ]; Argentina [GDB #3] one [ 84 ]; Colombia [GDB #5] one [ 85 ]) ( S5 Table ). Two studies represented the general population in a specific geographical area using a cross-sectional design [ 82 , 84 ], while two focussed on pregnant women (cross-sectional) [ 85 ] or women who recently gave birth (case control) [ 83 ], reflecting the importance of vertical infection transmission.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four papers on Chagas’ disease met the inclusion criteria (Brazil [GDB #1] two [ 82 , 83 ]; Argentina [GDB #3] one [ 84 ]; Colombia [GDB #5] one [ 85 ]) ( S5 Table ). Two studies represented the general population in a specific geographical area using a cross-sectional design [ 82 , 84 ], while two focussed on pregnant women (cross-sectional) [ 85 ] or women who recently gave birth (case control) [ 83 ], reflecting the importance of vertical infection transmission.…”
Section: Resultsmentioning
confidence: 99%
“…The Argentinian study compared self-reported Chagas and vector presence by SEP. In a region with horizontal control strategies, they found lower reported vector prevalence, higher self-reported Chagas prevalence, and smaller (and not statistically significant) educational inequalities in such prevalence than in a region with vertical control strategies [ 84 ]. The authors concluded that horizontal control strategies reduced vector prevalence, raised awareness of Chagas’ disease in all strata, and reduced inequalities in such awareness.…”
Section: Resultsmentioning
confidence: 99%
“…To this aim we elaborated a more comprehensive measure of socio-economic status since previous studies have focused on a few proxy variables: the goat-equivalent index [16], domicile’s characteristics (i.e., construction materials, size, cracks in walls, etc.) [26,29,30], and educational level [76]. The social vulnerability index summarized all of the above and also included household overcrowding, agricultural practices, at least one member with a stable source of income by employment, and the household number of welfare recipients [54].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, awareness of Chagas disease is limited among medical providers in the USA; 68.2% of American College of Obstetricians and Gynecologists surveyed described their knowledge level about Chagas disease as “very limited” [18]. Yet, in areas where the disease is endemic, such as Argentina, there have been high rates of public participation in vector control campaigns which indicate an awareness of risk of Chagas disease [19]. …”
Section: Discussionmentioning
confidence: 99%